Literature Study Of Histological Structure Of Female Pig Reproduction System - Oktaviano P.K Dekrismar; Cynthia Dewi Gaina; Filphin A Amalo (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
The female reproductive organs function to produce ovum cells (oocytes) and hormones. The female reproductive organs are also a place where the embryo grows and develops in the uterus. The reproductive organs in pigs consist of the ovaries, oviduct, uterus and vagina. The purpose of this literature study is to determine the histological structure of the ovaries, oviducts, uterus and vagina. This literature review was conducted to see the histological structure of the reproductive system of sows. The method used is a qualitative descriptive method with a literature study approach. Based on the results of the studies that have been done, it is known that the ovaries have a histological structure consisting of a cortex which contains several stages of follicles and a medulla consisting of blood vessels, connective tissue, lymphatics, and nerves. The ovaries are covered by a layer of cuboidal cells called the germinal epithelium and underneath is a layer of dense connective tissue called tunica albuginea. The oviduct structure consists of three layers, such as tunica mucosa, tunica muscularis and tunica serosa. The mucosa of the oviduct consists of simple columnar epithelium or pseudostrative with ciliated cells and there is also a longitudinal fold in this area. The muscularis tunica of the oviduct consists of two muscle layers, such as longitudinal muscle layer and the cycular muscle layer. The muscle layer of the isthmus is thickest and gradually thins toward the infundibulum. The outer layer of the oviduct is the serous tunica. The uterine structure consists of three layers, such as endometrium, myometrium and perimetrium.